Level of strength development of students involved in rock climbing sports sections using exercises on different simulators - Kateryna Mulyk; Tetiana Grynova; Alexander Skaliy; Sergey Bershov; Volodymyr Kornienko (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the influence of rock climbing classes according to different programs on the level of strength development of students involved in rock climbing sports sections. Material and methods: 45 student rock climbers (men) aged 18-23 participated in the study, who were engaged in rock climbing sections. The subjects were divided into three groups of 15 people each: the first - the control group (CG), included athletes who trained according to the standard method; the second - experimental group No. 1 (EG1), included athletes who trained according to a standard program with the inclusion of specially designed exercises for the development of strength on the campus board; the third - experimental group No. 2 (EG2), included athletes who went in for a standard program with the inclusion of specially selected exercises on gymnastic rings. To assess the level of strength development and its dynamics, tests were used that illuminate as closely as possible the manifestations of strength in climbing, namely: hanging in the block, pulling up on the bar, pulling up to the chest, flexion of the extension of the arms in the lying position, wrist dynamometry, flexion of the hand with weights. Results: in order to determine the influence of rock climbing lessons according to different programs on the level of strength development of students involved in rock climbing sports sections, an analysis of special indicators was carried out. So, it was revealed that the studied indicators in all groups during the experiment tended to improve. Conclusions: it was found that exercises on a campus board and gymnastic rings have an unequal effect on the development of individual muscle groups, which allows us to conclude that it is necessary to combine these programs to ensure the diversified development of the strength of students involved in rock climbing sports sections.